(untitled) (Colombia Medica, 2009)
Programmed cell death occurs as a physiological process during development. In the brain and spinal cord this event determines the number and location of the different cell types. In adulthood, programmed cell death or apoptosis is more restricted but it may play a major role in different acute and chronic pathological entities. However, in contrast to other tissues where apoptosis has been widely documented from a morphological point of view, in the central nervous system complete anatomical evidence of apoptosis is scanty. In spite of this there is consensus about the activation of different signal systems associated to programmed cell death. In the present article we attempt to summarize the main apoptotic pathways so far identified in nervous tissue. Considering that apoptotic pathways are multiple, the neuronal cell types are highly diverse and specialized and that neuronal response to injury and survival depends upon tissue context, (i.e., preservation of connectivity, glial integrity and cell matrix, blood supply and trophic factors availability) what is relevant for the apoptotic process in a sector of the brain may not be important in another.